Concomitant occurrence of anthropogenic air pollutants, mineral dust and fungal spores during long-distance transport of ragweed pollen. (November 2019) - Grewling, Łukasz; Bogawski, Paweł; Kryza, Maciej; Magyar, Donat; Šikoparija, Branko; Skjøth, Carsten Ambelas; Udvardy, Orsolya; Werner, Małgorzata; Smith, Matt
Abstract: Large-scale synoptic conditions are able to transport considerable amounts of airborne particles over entire continents by creating substantial air mass movement. This phenomenon is observed in Europe in relation to highly allergenic ragweed ( Ambrosia L.) pollen grains that are transported from populations in Central Europe (mainly the Pannonian Plain and Balkans) to the North. The path taken by atmospheric ragweed pollen often passes through the highly industrialised mining region of Silesia in Southern Poland, considered to be one of the most polluted areas in the EU. It is hypothesized that chemical air pollutants released over Silesia could become mixed with biological material and be transported to less polluted regions further North. We analysed levels of air pollution during episodes of long-distance transport (LDT) of ragweed pollen to Poland. Results show that, concomitantly with pollen, the concentration of air pollutants with potential health-risk, i.e. SO2, and PM10, have also significantly increased (by 104% and 37%, respectively) in the receptor area (Western Poland). Chemical transport modelling (EMEP) and air mass back-trajectory analysis (HYSPLIT) showed that potential sources of PM10 include Silesia, as well as mineral dust from the Ukrainian steppe and the Sahara Desert. In addition, atmospheric concentrations of other allergenic biological particles, i.e. Alternaria Nees ex Fr. spores, also increased markedly (by 115%) during LDT episodes. We suggest that the LDT episodes of ragweed pollen over Europe are not a "one-component" phenomenon, but are often related to elevated levels of chemical air pollutants and other biotic and abiotic components (fungal spores and desert dust). Graphical abstract: Image 1 Highlights: Long-distance transport (LDT) of ragweed pollen is a common phenomena in Europe. LDT episodes are associated to increased levels of SO2, PM10 and Alternaria spores. Alternaria spores are released concomitantly with pollen from agricultural sources. SO2 /PM10 mixes with the plume of pollen over industrialised regions of Southern Poland. Mineral dust originated from the Sahara is also present during LDT episodes.